PERANAN KELEMBAGAAN KELOMPOK USAHA PERHUTANAN SOSIAL HUTAN ADAT DI NEGERI HUTUMURI KECAMATAN LEITIMUR SELATAN KOTA AMBON - Lelapary, Jezenia; Silaya, Thomas; Iskar, Iskar (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Customary Forest is one of the social forestry schemes in the framework of sustainable forest management by utilizing indigenous communities as the main actors in order to improve welfare, environmental balance and socio-cultural dynamics. Customary Forest is a forest located within the territory of the customary law community. This study aims to examine the role of the Social Forestry Business Group (SFBG) and customary institutions in the management of Customary Forests in Hutumuri village.. The research method used was descriptive qualitative, with data collected through interviews and field observations. Sampling is done by purposive sampling where sampling is based on previously known characteristics or properties of the population (Sugiyono, 2016). The results showed that SFBG has an important role in managing forest resources sustainably and improving the welfare of local communities. SFBG functions in social forestry business development, compliance with regulations, supervision, evaluation, and reporting. The SFBG organizational structure includes a chairperson, secretary, treasurer, planning, implementation, and supervision, each with specific roles. Customary institutions also play an important role in the planning and implementation of institutional improvement programs, such as the inauguration of soa heads and saniri negeri, the establishment of SFBG, and training on forest product processing. In addition, there is a role in the application for the determination of customary forests to the Minister of Environment and Forestry, the location of customary forests belongs to the state or Soa, and the marking of boundaries involves each Soa. In conclusion, the synergy between SFBG and customary institutions is crucial for the successful management of Hutan Adat in Negeri Hutumuri.